2021
DOI: 10.26434/chemrxiv.13191617.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Selective Crystallization via Vibrational Strong Coupling

Abstract: The coupling of (photo)chemical processes to optical cavity vacuum fields is an emerging method for modulating molecular and material properties. Recent reports have shown that strong coupling of the vibrational modes of solvents to cavity vacuum fields can influence the chemical reaction kinetics of dissolved solutes. This suggests that vibrational strong coupling might also effect other important solution-based processes, such as crystallization from solution. Here we test this hither-to unexplored notion, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Recently Hirai et al reported that VSC of the solvent could drive selective crystallization of metal-organic frameworks (MOFs), suggesting that VSC can alter molecular organization. [20] Here we demonstrate that VSC modifies supramolecular assembly and its dynamics. We study the gelation of rigid-rod conjugated polymers under strong coupling.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…Recently Hirai et al reported that VSC of the solvent could drive selective crystallization of metal-organic frameworks (MOFs), suggesting that VSC can alter molecular organization. [20] Here we demonstrate that VSC modifies supramolecular assembly and its dynamics. We study the gelation of rigid-rod conjugated polymers under strong coupling.…”
mentioning
confidence: 63%
“…In the last several years, it has been shown that coupling vibrational modes in this way has a pronounced effect on chemistry and molecular properties. [3,[5][6][7][8][9][10][11][12][13][14][15][16][17]20] In this vibrational strong coupling regime (VSC), vibro-polaritonic states (VP + , VPÀ) are formed, separated by the so-called Rabi splitting energy (" h W R ) (Figure 1 a). In typical experiments, a large number N of molecules are coupled by VSC to a single optical mode which leads to the formation of N-1 dark states (DS) which are, together with VP + and VPÀ, delocalized over many molecules.…”
mentioning
confidence: 99%
“…The potential of cavity modified physical and chemical properties is extraordinary. The most exciting results in this field are the reports of VSC-modified chemistry in the dark, first published by Ebbesen and co-workers and later established by several of those authors in new roles as independent investigators, , as well as by other unaffiliated researchers. , The methodologies these papers present appear to be robust. They include appropriate controls, repeated measurements, and reasonable attempts to rationalize the observations.…”
Section: Discussionmentioning
confidence: 99%
“…These challenges call attention to the advantages of nonoptical interrogation. We will highlight the use of electrochemical cycling, , mass spectrometry, nuclear magnetic resonance, and phase change processes as alternative means for monitoring cavity chemistry. One critical concern for these physical measurements, however, is the correlation between the locality of the measurement and the cavity resonance at that location.…”
Section: Experimental Difficulties and Pitfallsmentioning
confidence: 99%
“…Vibrational polaritons [1][2][3], quasi-particles formed by coupling molecular vibrations and radiation modes in an optical cavity, exhibit a wide range of exotic phenomena. A series of recent experiments [1][2][3][4][5][6][7][8] have demonstrated that chemical kinetics can be enhanced [4,6,8] or suppressed [1,5], molecular bonds can be selectively broken [2], and selective crystallization can be achieved [9] via the formation of vibrational polaritons. On the other hand, several studies [10,11] have also reported possible discrepancies or inconsistencies in the interpretation of experiment purporting sizable kinetic effects.…”
Section: Introductionmentioning
confidence: 99%